Draft Annual Plan 1987-88 Part -I- Plan in Outline Summary of Sectoral Outlays and Statistical Statements Government of Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1986)
The year 1987—88 is the third year of the Seventh Five Year Plan. During, the first two years investment has been stepped up proportionately from Rs 64.00 crores in 1985—86 to Rs.73.00 crores in 1986—87. During the year 1985-86 the actual plan expenditure incurred was Rs. 64.73 crores. During the current year the expenditure up to the 2nd quarter ended September 1986 is expected to be around Rs. 25.71 crores, which is about 35% of the approved outlay.
Government of Union Territory of Goa, Daman and Diu, Directorate of Planning, Statistics and Evaluation